Mass-loading and non-spherical divergence in hot galactic winds: implications for X-ray observations. Issue 4 (8th October 2021) - Nguyen, Dustin D; Thompson, Todd A
ABSTRACT: Cool clouds are expected to be destroyed and incorporated into hot supernova-driven galactic winds. The mass-loading of a wind by the cool medium modifies the bulk velocity, temperature, density, entropy, and abundance profiles of the hot phase relative to an unmass-loaded outflow. We provide general equations and limits for this physics that can be used to infer the rate of cool gas entrainment from X-ray observations, accounting for non-spherical expansion. In general, mass-loading flattens the density and temperature profiles, decreases the velocity and increases the entropy if the Mach number is above a critical value. We first apply this model to a recent high-resolution galactic outflow simulation where the mass-loading can be directly inferred. We show that the temperature, entropy, and composition profiles are well matched, providing evidence that this physics sets the bulk hot gas profiles. We then model the diffuse X-ray emission from the local starburst M82. The non-spherical (more cylindrical) outflow geometry is directly taken from the observed X-ray surface brightness profile. These models imply a total mass-loading rate that is about equal to that injected in the starburst ≃ 10 M⊙ yr −1, and they predict an asymptotic hot wind velocity of $\sim 1000\, {\rm km \ s^{-1}}$, which is ∼1.5–2 times smaller than previous predictions. We also show how the observed entropy profile can be used to constrain the outflow velocity, making predictions for future missions like XRISM. We argue that the observed X-ray limb brightening may be explained by mass-loading at the outflow's edges.